2021
DOI: 10.1101/2021.08.12.21261929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 antibodies six months into the vaccination campaign in Geneva, Switzerland

Abstract: Background: Up-to-date seroprevalence estimates are critical to describe the SARS-CoV-2 immune landscape in the population and guide public health measures. We aimed to estimate the seroprevalence of anti-SARS-CoV-2 antibodies 15 months into the COVID-19 pandemic and six months into the vaccination campaign. Methods: We conducted a population-based cross-sectional serosurvey between June 1 and July 7, 2021, recruiting participants from age- and sex-stratified random samples of the general population. We tested… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
0
23
1
1
Order By: Relevance
“…Between April 29 th and June 9 th , 2022, we recruited participants from a random sample of individuals aged ≥6 months provided by the cantonal population registry (Office cantonal de la population et des migrations), and from an age-and sex-stratified random sample of adults who participated in at least one of our previous serosurveys (Supplementary figure 2) (20)(21)(22). Newly selected individuals were invited by letter, while returning participants were invited by letter or email when available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between April 29 th and June 9 th , 2022, we recruited participants from a random sample of individuals aged ≥6 months provided by the cantonal population registry (Office cantonal de la population et des migrations), and from an age-and sex-stratified random sample of adults who participated in at least one of our previous serosurveys (Supplementary figure 2) (20)(21)(22). Newly selected individuals were invited by letter, while returning participants were invited by letter or email when available.…”
Section: Methodsmentioning
confidence: 99%
“…With a population of about 500000, the canton of Geneva, Switzerland, has had 261946 confirmed cases (448 per 1000 inhabitants) and 883 deaths reported by July 21 st , 2022 (19). Our previous serosurvey revealed that by June-July 2021, around two thirds of the population had developed anti-SARS-CoV-2 antibodies following vaccination and/or infection, half of which having antibodies of infection origin (20). Since then, eligibility for vaccination against COVID-19 has progressively expanded in Geneva to cover most age groups, including ages 12-15 years since June 2021 and ages 5-11 years since January 2022 (Supplementary figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Desde el inicio de la pandemia, en marzo de 2020, y hasta el momento en que se redacta este artículo, se han notificado alrededor de 10 millones de infectados, habiendo indicios de que la cifra real puede ser de incluso el doble 9 . En la figura 1 se 10 muestra la evolución de la tasa de incidencia acumulada a 14 días y de la tasa de mortalidad acumulada a 14 días, distinguiéndose seis ciclos de pandemia que, a efectos prácticos para este artículo, simplificamos en cuatro periodos en función de sus efectos sobre los valores nucleares antes descritos en la AP.…”
Section: El Impacto Sobre La Atención Primaria De Las Distintas Olas ...unclassified
“…Considering an approximate prevalence of 25% at that stage in the pandemic [29], this would correspond to a positive predictive value (PPV) of 100%, a negative predictive value (NPV) of 86•06% and a diagnostic accuracy of 87•85%. Finally, the receiver operating characteristic curve (AUROC) is 0•9940 (95% CI: 0•9873-1•000) (Fig.…”
Section: Sample Validation In Serummentioning
confidence: 99%